Urban Agriculture and its Sustainability Implications on the Food-Water-Energy Nexus - Jiangxiao Qiu; Hui Zhao; Lorna Bravo; Jessica Ryals (EDIS, 2023)
Urban agriculture has the potential to contribute to urban sustainability through its interactions with food, water, and energy (FEW) resource flows, and thus needs to be evaluated and analyzed through an integrative rather than a siloed approach. This publication provides an overview of the concept of FEW nexuses in the urban context and describes the role of urban agriculture and its sustainability implications for FEW nexuses and resources. Specific local case studies provide examples. This publication provides a holistic, interdisciplinary lens to understand the crucial role and sustainability implications of urban agriculture, currently gaining momentum in the global research and policy agenda. The fact sheet should be useful to urban and regional planners and policy-makers engaged in the development of urban agriculture, as well as to Extension agents seeking to communicate the sustainability implications of urban agriculture.